METHODOLOGICAL ISSUES OF ORGANIZING GREEN EDUCATION (Education in the 21st Century, 2024)
The demand for green education is increasing dramatically as the planet's population grows. Humans cause enormous damage to the planet earth with their actions and domestic activities. Pursuing private interests, individuals generally do not pay attention to the negative consequences of their activities on the environment, which ultimately creates environmental and social risks, disrupts the sustainable development of the economy. In this regard, the development of a green education methodology that targets the lifelong learning of individuals is highlighted. Therefore, the present problem is the effective organization of green education in such a way that it continuously accompanies the individual throughout his life and has flexible transformational basis among different age groups. In the article, recommendations are made in terms of improving the methodological directions of green education in such a way that an educational environment conducive to green practices is formed around the individual throughout his life in formal, non-formal and informal ways.
Keywords: green education; sustainable development; green behavior; environmental protection; ecofriendly; formal, non-formal and informal education